Locust and grasshopper outbreaks in Zululand sugarcane, Kwazulu-Natal, South Africa - Bam, Adrian Jock (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScConEcol)--Stellenbosch University, 2014.